Autism Awareness Scale for Security Officers Working in Hospitals: A Study of Validity and Reliability - SARISALTIK, ALİCAN; ILGIN, CAN; SAVE, DİLŞAD; KARAVUŞ, MELDA; LÜLECİ, NİMET EMEL; HIDIROĞLU, SEYHAN (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: The purpose of this study was to evaluate the knowledge and awareness toward autism among security officers working in hospitals and to explore the validity and reliability of the Autism Awareness Scale for Security Officers (AASSO) developed by the researchers. Methods: This methodological study was conducted at two Government Training and Research Hospitals in Istanbul, Turkey. A total of 135 security officers were included in the study and the data were obtained between February and April 2019. The AASSO is a 4-point Likert type scale and consists of 20 items. The factor structure of the scale was extracted by performing exploratory factor analysis. Results: Most of the participants were male (n=79; 58.5%) and high school graduates (n=86; 67.7%). Participants considered autism mostly as a kind of mental retardation (n=69; 51.9%), followed by social interaction problem (n=24; 18.0%). The AASSO reduces autism awareness into 3 factors ('Coming across', 'Communication' and `Interaction with the environment'), with eigenvalues ranging from 9.417 to 1.201 and explained 65.45% of all variance. Cronbach's alpha values for the AASSO was 0.936 and ranged from 0.921 to 0.809 for the subscales. Conclusion: According to these results AASSO is a valid and reliable scale. The consequence of further studies especially conducted on non-healthcare professionals of hospitals should be establishing autism-friendly hospitals.
Keywords: Autism; awareness; reliability; scale; validity